Molecular-cytogenetic studies of ribosomal genes and heterochromatin reveal conserved genome organization among 11 Quercus species (TAG Theoretical and Applied Genetics, 1999)
Genomes of 11 Quercus species were characterized using cytogenetic (Giemsa C-banding, fluorochrome banding), molecular-cytogenetic (fluorescence in situ hybridization, FISH, to ribosomal genes) and molecular (dot-blot for ribosomal gene-copy number assessment) techniques. Ribosomal genes are the first DNA sequences to be physically mapped in oaks, and the copy number of the 18S-5.8S-26 S rRNA genes is estimated for the first time. Oak karyotypes were analysed on the basis of DAPI banding and FISH patterns; five marker chromosomes were found. In addition, chromosomal organization of ribosomal genes with respect to AT- and GC-differentiated heterochromatin was studied. Fluorochrome staining produced very similar CMA/DAPI banding patterns, and the position and number of ribosomal loci were identical for all the species studied. The 18S-5.8S-26 S rRNA genes in oak complements were represented by a major locus at the subterminal secondary constriction (SC) of the only subtelocentric chromosome pair and a minor locus at paracentromeric SC of one metacentric pair. The only 5 S rDNA locus was revealed at the paracentromeric region of the second largest metacentric pair. A striking karyotypic similarity, shown by both fluorochrome banding and FISH patterns, implies close genome relationships among oak species no matter their geographic origin (European or American) or their ecophysiology (deciduous or evergreens). Dot-blot analysis gave preliminary evidence for different copy numbers of 18S-5.8S-26 S rRNA genes in diploid genomes of Q. cerris, Q. ilex, Q. petraea, Q. pubescens and Q. robur (2700, 1300, 2200, 4000 and 2200 copies, respectively) that was correlated with the size polymorphism of the major locus.